Return of the native facilitated by the invasive? Population composition, substrate preferences and epibenthic species richness of a recently discovered shellfish reef with native European flat oysters (Ostrea edulis) in the North Sea. Issue 6 (3rd July 2018) - Christianen, M. J. A.; Lengkeek, W.; Bergsma, J. H.; Coolen, J. W. P.; Didderen, K.; Dorenbosch, M.; Driessen, F. M. F.; Kamermans, P.; Reuchlin-Hugenholtz, E.; Sas, H.; Smaal, A.; van den Wijngaard, K. A.; et al.
ABSTRACT: After being ecologically extinct for almost a century, the discovery of a shellfish reef with native European flat oysters ( Ostrea edulis ) in the Dutch coastal area of the North Sea by the authors of this study called for an extensive survey to better understand some of the key requirements for the return of the native oyster in coastal waters. We assessed habitat conditions, its potential for increasing biodiversity, and the role of substrate provision by other bivalves such as the invasive alien Pacific oyster ( Crassostrea gigas ). Using underwater visual census, O. edulis size-frequency distributions and attachment substrate was investigated, as well as the composition of the epibenthic community and substrata types inside quadrats that were distributed across the reef. This reef was found to be composed of native European flat oysters, invasive alien Pacific oysters and blue mussels ( Mytilus edulis ), alternated with sandy patches. The O. edulis population (6.8 ± 0.6 oysters m −2 ) consisted of individuals of different size classes. In quadrats with native and non-native oysters the number of epibenthic species was 60% higher compared to adjacent sand patches within the reef. Notably, our results showed that the native oyster predominantly used shell (fragments) of the invasive Pacific oyster as settlement substrate (81% of individuals). Our results optimistically show that conditions for native oyster restoration can be suitable at a local scale in the coastal North Sea area and suggest that the return of native oysters may be facilitated by novel substrate provided by invasive oysters at sites where their distribution overlap.